2.7-kV AlGaN/GaN Schottky barrier diode on silicon substrate with recessed-anode structure. (January 2021) - Xu, Ru; Chen, Peng; Liu, Menghan; Zhou, Jing; Li, Yimeng; Liu, Bin; Chen, Dunjun; Xie, Zili; Zhang, Rong; Zheng, Youdou
Highlights: The rapid etch process results in improving etching quality with a 0.26-nm roughness of the anode recess surface. Proper post-modification is essential to the device performance. With the optimized process, 2.7-kV AlGaN/GaN Schottky barrier diode on silicon were fabricated. Abstract: In this paper, we demonstrate high-performance lateral AlGaN/GaN Schottky barrier diodes (SBD) on Si substrate with a recessed-anode structure. The optimized rapid etch process provides results in improving etching quality with a 0.26-nm roughness of the anode recessed surface. By using the high work function metal Pt as the Schottky electrode, a low turn-on voltage of 0.71 V is obtained with a high uniformity of ±0.023 V for 40 devices. Supported by the flat anode recess surface and related field plate design, the SBD device with the anode–cathode spacing of 15 μm show the specific on-resistance ( Ron, sp ) of 1.53 mΩ·cm 2 only, the physical breakdown voltage can reach 1678 V with a high power figure-of-merit (P-FOM) of 1840 MW/cm 2 . For the SBD device with the anode–cathode spacing of 30 μm, the physical breakdown voltage can be as high as 2705 V and the power FOM is 2217 MW/cm 2 .